Environmental impact on the bacteriological quality of domestic water supplies in Lagos, Nigeria - Egwari L; Aboaba O O (Universidade de São Paulo, 2002)
OBJECTIVE: To assess the impact of town planning, infrastructure, sanitation and rainfall on the bacteriological quality of domestic water supplies. METHODS: Water samples obtained from deep and shallow wells, boreholes and public taps were cultured to determine the most probable number of Escherichia coli and total coliform using the multiple tube technique. Presence of enteric pathogens was detected using selective and differential media. Samples were collected during both periods of heavy and low rainfall and from municipalities that are unique with respect to infrastructure planning, town planning and sanitation. RESULTS: Contamination of treated and pipe distributed water was related with distance of the collection point from a utility station. Faults in pipelines increased the rate of contamination (p<0.5) and this occurred mostly in densely populated areas with dilapidated infrastructure. Wastewater from drains was the main source of contamination of pipe-borne water. Shallow wells were more contaminated than deep wells and boreholes and contamination was higher during period of heavy rainfall (p<0.05). E. coli and enteric pathogens were isolated from contaminated supplies. CONCLUSIONS: Poor town planning, dilapidated infrastructure and indiscriminate siting of wells and boreholes contributed to the low bacteriological quality of domestic water supplies. Rainfall accentuated the impact.